Polish adaptation and validation of the Perceived Implicit Rationing of Nursing Care (PIRNCA) questionnaire: a cross-sectional validation study - Izabella Uchmanowicz; Joanna Rosińczuk; Aleksandra Kołtuniuk; Agnieszka Młynarska; Katarzyna Łagoda; Izabela Witczak; Terry Jones (BMJ Open)
Objectives To develop a Polish adaptation of the Perceived Implicit Rationing of Nursing Care (PIRNCA)questionnaire.Design Cross-sectional validation study.Settings Nurses working in surgical and cancer wards in Poland.Participants A sample of 513 professionally active nurses was enrolled in the study.Intervention To complete a Polish translation of the full original PIRNCA questionnaire.Primary and secondary outcome measures The primary outcome was translation and adaptation of the full original PIRNCA tool and its validation to the Polish conditions. The secondary outcome was determination of relationships between sociodemographic variables, nurses’ assessment of patient care quality and their overall job satisfaction on the one hand, and PIRNCA scores on the other.Results The respondents’ mean score was 1.27 points (SD=0.68) on a scale from 0 to 3. Cronbach’s alpha for the entire instrument was 0.957. All items of the questionnaire were found to have a positive item-total correlation. The developed linear regression model showed that nurses’ assessment of patient care quality and their overall job satisfaction were independent predictors of PIRNCA scores (p<0.05). 94.15% of nurses reported rationing at least one of the 31 care activities.Conclusions The present findings indicate a high level of reliability and validity of the translated PIRNCA questionnaire, fully comparable to that of the original. The questionnaire can be used for the assessment of PIRNCA in Polish hospitals.